The effect of distributed generator injection in different number of units on power and voltage losses in the electricity distribution system - Syukri, Mahdi; Nasution, Ardiansyah (Journal Geuthee of Engineering and Energy, 2024)
Distributed Generator (DG) is a small-capacity power plant located within the electrical distribution system and is usually placed on buses directly connected to the load. The placement of distributed generators is a technical effort to reduce voltage drops and power losses in the system. Additionally, Power flow analysis is conducted to plan and determine the power levels within an electrical power system. The results in terms of power losses after adding a DG were achieved in the fifth experiment on bus 149, where the system's total active power loss (P) decreased from 720.822 kW to 682.939 kW, and the total reactive power loss (Q) decreased from 530.02 kVar to 405.835 kVar. These results were obtained from power flow calculations using Electrical Transient Analyzer Program (ETAP) software.Therefore, it can be concluded that the electrical network system is operating efficiently. The results show that the more wind turbine generators are added to the buses, the more the voltage drop is reduced. After simulation, the overall voltage drops still meet the standards according to the text report in ETAP.